The Mote of Mark A Dark Age Hillfort in South-West Scotland - Laing, Lloyd (Oxbow Books, 2006)
The Mote of Mark is a low boss of granite rising from forty-five metres above the eastern shore of Rough Firth, where the Urr Water enters the Solway, between the villages of Kippford and Rockcliffe. The summit comprises a central hollow between two raised areas of rock and was formerly defended by a stone and timber rampart enclosing one third of an acre. The Mote of Mark appears to have first attracted the attention of antiquaries in the late eighteenth century, and first assumed national importance with Alexander Curle's major work in 1913. After the interruption of the First World War, the site was left largely alone until it was re-excavated in the 1970s. These excavations, in 1973 and '79 were designed to answer three specific questions: How many phases of activity are represented in the structural history of the defences? How many phases of activity are represented by the evidence for Early Medieval metalworking and occupation? And, how does the evidence of occupation within the defences relate to the structural history of the defences? This book presents the results of the excavations and their interpretation within the framework of these questions.